2021
DOI: 10.3389/fpsyt.2021.639393
|View full text |Cite
|
Sign up to set email alerts
|

Reorganization of Substance Use Treatment and Harm Reduction Services During the COVID-19 Pandemic: A Global Survey

Abstract: Background: The coronavirus disease 2019 (COVID-19) pandemic has impacted people with substance use disorders (SUDs) worldwide, and healthcare systems have reorganized their services in response to the pandemic.Methods: One week after the announcement of the COVID-19 as a pandemic, in a global survey, 177 addiction medicine professionals described COVID-19-related health responses in their own 77 countries in terms of SUD treatment and harm reduction services. The health responses were categorized around (1) m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 40 publications
1
49
0
Order By: Relevance
“…These could be valuable and applicable avenues to explore digitally to enhance prosocial affinity among adolescents and curb alcohol consumption. In light of the shifting psychiatric health provision in many countries (55), these linkages presented the necessity to maintain addiction services, particularly toward the subgroup of vulnerable adolescents.…”
Section: Alcoholmentioning
confidence: 99%
“…These could be valuable and applicable avenues to explore digitally to enhance prosocial affinity among adolescents and curb alcohol consumption. In light of the shifting psychiatric health provision in many countries (55), these linkages presented the necessity to maintain addiction services, particularly toward the subgroup of vulnerable adolescents.…”
Section: Alcoholmentioning
confidence: 99%
“…Here, we report results from the first round of the ISAM global survey on drug and alcohol use, price, supply, and complications during the COVID-19 pandemic. Data related to the second section of the survey concerning substance use treatment and harm reduction services responses to the pandemic have been published recently (18). We hypothesized that drug and alcohol use would increase, prices would increase, supply would decrease, and complications would increase and that results would differ by region (given the differential spread of COVID-19 and regional responses to the COVID-19 pandemic).…”
Section: Introductionmentioning
confidence: 99%
“…Other mitigation measures that were introduced during periods when social restrictions were in place were increasing dispensing of take-home medications such as methadone. In the results section we noted that two of the included studies examined increases in the provision of take-home medication (OAT) during the initial stages of the pandemic and found there to be few negative consequences associated with this in terms of diversion of medication [52][53][54]. These are interesting findings as the issue of non-supervised consumption of OAT is a contested topic and especially relating to concerns over the diversion of medication and potential increased risk of overdose [78].…”
Section: Reduced Access To Treatment and Harm Reduction Servicesmentioning
confidence: 93%
“…Several studies reported reduced access to harm reduction services owing to the pandemic [48,52,61] though only one study inferred that this was related to a subsequent rise in DRDs [41]. More recent research has provided further evidence of the impacts of reduced service access including reductions in uptake of injecting equipment and MAT as well as a reduction of uptake of HIV and other BBV testing in Spain, UK and Sweden [75][76][77].…”
Section: Reduced Access To Treatment and Harm Reduction Servicesmentioning
confidence: 99%